(untitled) (Texas Journal of Engineering and Technology, 2022)
The article presents the results of theoretical studies on the study of the oscillatory motion of a tandem roller in the longitudinal-vertical plane, while to ensure the high quality of the tandem roller, the amplitude of its forced oscillations should have a minimum value, and it is emphasized that in practice this is mainly ensured by the correct choice of the longitudinal distance from the center of rotation of the slatted and tubular roller to the “O” hinge, as well as the number of slats and tubes installed on the rollers.